2008
DOI: 10.1097/01.aog.0000296654.43944.e6
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of Women After a First Episode of Postmenopausal Bleeding and Endometrial Thickness Greater Than 4 Millimeters

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…23,97 The majority of studies defined the primary outcome as an improvement in symptoms of AUB as perceived by the patient. All of the studies 23,75,91,97,101,[105][106][107][108][109][110][111][112][113][114][115] (plus TJ Clark, unpublished) reported an improvement in symptoms from 60% to 100%. The study looking exclusively at postmenopausal patients presented a survival analysis curve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,97 The majority of studies defined the primary outcome as an improvement in symptoms of AUB as perceived by the patient. All of the studies 23,75,91,97,101,[105][106][107][108][109][110][111][112][113][114][115] (plus TJ Clark, unpublished) reported an improvement in symptoms from 60% to 100%. The study looking exclusively at postmenopausal patients presented a survival analysis curve.…”
Section: Discussionmentioning
confidence: 99%
“…The 17 studies 23,75,91,97,101,[105][106][107][108][109][110][111][112][113][114] (including TJ Clark, Birmingham Women's Hospital, 2013, unpublished) that met our inclusion criteria enrolled a total of 1829 patients between 1989 and 2009. The population size ranged from 8 to 311, with only five studies having a population size of > 100.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A multicentre study by Ferrazzi et al (2009) found only one case of a grade-1 endometrial cancer in 1152 asymptomatic women with endometrial polyps. Another cohort study found no difference in the recurrence rate of PMB between those women who had a polypectomy, those who had a normal hysteroscopy, and those patients who had just office endometrial sampling (Timmermans et al, 2008). Ultimately, the decision as to whether a polyp is removed or not needs to be made in secondary care.…”
Section: Endometrial and Cervical Polypsmentioning
confidence: 99%